A NS-2 simulation model for DNP3 protocol over IEEE 802.15.4 wireless protocol toward low cost simulation of Smart Grid applications - Silva Pereira, Cassia Correia da [UNESP]; Shinoda, Ailton Akira [UNESP]; Oliveira, Ruy de; Nascimento, Valtemir E. do; Ferreira, Ed' Wilson T. (Ieee, 2014)
Faced with an imminent restructuring of the electric power system, over the past few years many countries have invested in a new paradigm known as Smart Grid. This paradigm targets optimization and automation of electric power network, using advanced information and communication technologies. Among the main communication protocols for Smart Grids we have the DNP3 protocol, which provides secure data transmission with moderate rates. The IEEE 802.15.4 is another communication protocol also widely used in Smart Grid, especially in the so-called Home Area Network (HAN). Thus, many applications of Smart Grid depends on the interaction of these two protocols. This paper proposes modeling, in the traditional network simulator NS-2, the integration of DNP3 protocol and the IEEE 802.15.4 wireless standard for low cost simulations of Smart Grid applications.
Keywords: DNP3; IEEE 802.15.4; NS-2; Smart Grid